Android-Based Horspool Algorithm for Proverb Search - Andri Agus Yahya (Cattleya Darmaya Fortuna, 2019)
A proverb is a sentence or group of words that expresses a purpose or will, a state of a person, or a thing that says the behavior, actions, and things about a person that, although indirect, expresses something that the reader or listener can understand. Horspool algorithm simplifies the boyer-Moore algorithm, which in this text search is searched in large text to find the first pattern. Since the text sought can be so large (allowing hundreds of thousands of characters), it is essential to use more efficient techniques. Based on this, an android-based proverb search application was created to make it easier for someone to find proverbs because not everyone understands them, making it more practical and efficient in terms of its use without having to carry sayings in the form of print media such as books.